Nothing Stays the Same: A Typology of Markers and Functions of Reimagination - SF. Luthfie Arguby Purnomo; Wildi Adila; Shabrina An Adzhani (Wacana Seni Journal of Arts Discourse, 2023)
Reimagination has become a common practice in milking the revenues of comics, animated films, films, and games that experienced a past glory. However, the discussions over reimagination specifically on its markers and a typology of functions remain under investigated. In response to this gap, we investigated 31 reimagined titles from comics, animated films, films, and games by implementing the theories of space and place reimagination by Richardson (2012), the death of the reader by Gray, Sandvoss, and Harrington (2007), transtylisation by Genette (1997), and narrative identity by Ricoeur (1991). The findings indicate that reimagined works have two shared markers namely mutation and presentness on the textual, visual, and operative elements of the works. Mutation deals with the alterations of the three elements while preserving the core narrative identity of the works while presentness refers to the adjustment of the three elements in chronospatial context of the present time. The investigated works also indicate that six reimagination functions could be formulated. Those functions are stylistic, ludic, methectic, medial, branding, and cultural reimaginations.